Empowering education of arthroplasty patients' significant others in three Southern European countries - Copanitsanou, Panagiota; Sourtzi, Panayota; Cano, Sara; Cabrera, Esther; Charalambous, Andreas; Katajisto, Jouko; Leino-Kilpi, Helena; Papastavrou, Evridiki; Valkeapää, Kirsi; Zabalegui, Adelaida; Lemonidou, Chryssoula (My University, 2018)
Aims and objectives: To examine the relationship between significant others' expected and received knowledge and their background characteristics in three Mediterranean countries (Cyprus, Greece, Spain), all of which deal with economic restrictions, have similar social support systems with the family members acting as family caregivers, and cultural similarities. Background: Significant others' role is a key element in the older patients' postoperative recovery. However, people who take care of persons older than 65 years, as persons undergoing arthroplasty, are usually old themselves and need special support. Design: Multicentre, descriptive, correlational study. Methods: Data were collected preoperatively from 189 and postoperatively from 185 significant others using the Knowledge Expectations and the Received Knowledge of Significant Others Scales during 2010-2012. Results: Approximately one-fourth of the significant others were older than 65 years. Their knowledge expectations were not adequately addressed in any of the countries; they expected to be educated more on biophysiological issues and received the lowest knowledge regarding financial issues. The highest difference between expected and received knowledge was found in Greece and the lowest in Cyprus. Significant others may be less prepared for dealing with situations at home due to the knowledge difference between expected and received knowledge. Conclusions: Significant others receive less education comparing to what they expect; therefore, they are not prepared for dealing with problematic situations during their old relative's recovery. This is especially important in Mediterranean countries, where family members often provide patient care. Implications for practice: As health care is changing towards active participation of patients and family, it is important that nurses provide the education needed, as lower education may lead to poor patient outcomes and higher education may lead to significant others' anxiety. Nurses may keep in mind that older significant others do not report higher knowledge difference, but may have lower expectations.
Keywords: Arthroplasty; Empowerment; Family; Significant others; Surgery